2020
DOI: 10.31243/ei.uta.v5i4.966.2020
|View full text |Cite
|
Sign up to set email alerts
|

Influencia Del Estilo De Vida en El Estado De Salud De Los Adultos Mayores.

Abstract: Introducción: El estilo de vida es aquella elección consciente o inconsciente de practicar ciertos comportamientos que se van adquiriendo con el paso del tiempo y que en ocasiones son difíciles de modificar, influyendo principalmente en la salud. Objetivo: Analizar el estilo de vida y su influencia en el estado de salud de los adultos mayores del Sector la Unión, Provincia de Cotopaxi, Ecuador. Métodos: Estudio cuantitativo, correlacional, transversal, con una muestra censal de 35 adultos mayores, se aplicó el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
0
0
Order By: Relevance
“…(14) In South America, a study conducted in Ecuador insulting 35 older adults in the province of Cotopaxi, pointed out that the good lifestyle prevailed with a significant difference in relation to the fantastic and regular lifestyle, in the diet most consume hypo sodium and low-fat diets, maintain an adequate weight, Occasional self-medication and 43 % have body pain that makes their work a little difficult. (15) In Peru, a study conducted in Lima of 82 older adults revealed that 36,6 % have unhealthy nutrition, 58,5 % unhealthy and 4,9 % have healthy nutrition; taking into account, in terms of measurements, we found that unhealthy lifestyle predominated; in terms of nutrition; A healthy lifestyle prevails to the extent of physical activity. (16) Therefore, the objective of the research is to determine the lifestyle in teachers of older adults and nursing intervention during the COVID-19 pandemic in North Lima.…”
Section: Introductionmentioning
confidence: 58%
“…(14) In South America, a study conducted in Ecuador insulting 35 older adults in the province of Cotopaxi, pointed out that the good lifestyle prevailed with a significant difference in relation to the fantastic and regular lifestyle, in the diet most consume hypo sodium and low-fat diets, maintain an adequate weight, Occasional self-medication and 43 % have body pain that makes their work a little difficult. (15) In Peru, a study conducted in Lima of 82 older adults revealed that 36,6 % have unhealthy nutrition, 58,5 % unhealthy and 4,9 % have healthy nutrition; taking into account, in terms of measurements, we found that unhealthy lifestyle predominated; in terms of nutrition; A healthy lifestyle prevails to the extent of physical activity. (16) Therefore, the objective of the research is to determine the lifestyle in teachers of older adults and nursing intervention during the COVID-19 pandemic in North Lima.…”
Section: Introductionmentioning
confidence: 58%
“…En cuanto a la valoración del estilo de vida en la población ecuatoriana se analizó el estilo de vida de 35 adultos mayores del sector La Unión en la provincia de Cotopaxi, Ecuador. Para el estudio se aplicó el test fantástico y como resultado final se identificó que la población estudiada mantiene de forma general un estilo de vida dentro de los parámetros establecidos como adecuado, no obstante se pudo evidenciar la necesidad de promoción para la salud debido al consumo insuficiente de verduras y frutas, consumo frecuente de café entre los hábitos más perjudiciales identificados (Toapaxi et al, 2020). Estos datos se pueden contrastar con los resultados obtenidos en nuestra investigación donde coinciden los resultados de una nutrición inadecuada en los beneficiarios del estudio; en cuanto a elementos como el estrés, el sueño, control de la salud y conducta sexual no son elementos relevantes en el estudio realizado en la población de adultos mayores mencionado, pero sí fueron encontrados en el nuestro.…”
Section: Tablaunclassified
“…Evidenciando además que existen valores estadísticamente significativos que determinan que el generó influye en la funcionalidad familiar como también en los estilos de vida. (Toapaxi et al, 2020).…”
Section: Discusión De Los Demográficosunclassified